The Role of Adolescents in Preventing Non-Communicable Diseases - Afifah Viramita; Ning Arti Wulandari; Ulfa Husnul Fata; Yeni Kartika Sari (Health Gate, 2026)
The incidence of Non-Communicable Diseases (NCDs) is predicted to reach 52 million people in 2030, which has an impact on decreasing the productivity and quality of the nation's generation. Early intervention through the role of community nurses is very necessary, especially in adolescent groups in Islamic boarding schools. This activity aims to increase preventive awareness and early detection capabilities of NCDs in students through promotive and preventive efforts. This research method uses a Pre-Experimental method with a One Group Pretest, Posttest design. From a population of 80 students and 9 health cadres of students in " Islamic boarding school environment and a sample of 57 regular student respondents and 8 health cadres , by accidental sampling. The research instrument is a knowledge and attitude questionnaire, analyzed by the Wilcoxon Sign Rank Test. implementation includes health education with lecture and question and answer methods, health screening (blood pressure and Body Mass Index), and training of health cadres of students in blood pressure measurement techniques. This activity was conducted on December 15, 2025. The results showed a statistically significant increase in knowledge after the education program. Respondents' behavior in the good category increased from 29 to 43 (n=57). Rresults detected adolescents with pre-hypertension and overweight. Skills training successfully improved partners' competence in independently measuring blood pressure. In conclusion, providing health education and routine screening is effective in increasing knowledge, changing health behavior, and is a crucial first step in controlling NCD risk factors among adolescents.